2015
DOI: 10.1021/acs.analchem.5b02385
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Acidic Species of a Monoclonal Antibody Using Weak Cation Exchange Chromatography and LC-MS

Abstract: Charge variants, especially acidic charge variants, of recombinant monoclonal antibodies have been challenging to fully characterize despite the fact that several posttranslational modifications have already been identified. The acidic species of a recombinant monoclonal antibody were collected using weak cation exchange (WCX)-10 chromatography and characterized by LC-MS at multiple levels. In this study, methionine oxidation and asparagine deamidation are the only two modifications identified in the acidic sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 32 publications
(76 reference statements)
0
23
0
Order By: Relevance
“…The same retention time indicates that variants detected in the drug substance are likely the same as those generated from stressing the samples. 95 However, there are also cases where the degradation products generated during the process are different from those generated from forced degradation studies. A study demonstrated that oxidation of a drug substance resulted in oxidation of methionine residues preferentially on the same heavy chain while incubation with hydrogen peroxide resulted in oxidation of methionine residues randomly on the two heavy chains.…”
Section: Product-variant and Degradation Product Identificationmentioning
confidence: 99%
“…The same retention time indicates that variants detected in the drug substance are likely the same as those generated from stressing the samples. 95 However, there are also cases where the degradation products generated during the process are different from those generated from forced degradation studies. A study demonstrated that oxidation of a drug substance resulted in oxidation of methionine residues preferentially on the same heavy chain while incubation with hydrogen peroxide resulted in oxidation of methionine residues randomly on the two heavy chains.…”
Section: Product-variant and Degradation Product Identificationmentioning
confidence: 99%
“…7 Deamidated and non-modified species can therefore be distinguished by using adequate charge-sensitive separation techniques. 20,26,[30][31][32] The gold standard for identification of deamidated forms is peak collection after separation, followed by proteolytic digestion and peptide mapping.…”
Section: Deamidation and Isomerisationmentioning
confidence: 99%
“…The similarity of the charge profiles after Carboxypeptidase B digestion suggests that common modifications irrespective of cell line differences contribute to the charge profiles. Studies have also demonstrated that the charge profiles of recombinant monoclonal antibodies from cell cultures are very similar to the charge profiles obtained from incubation of purified main peak in slightly basic buffers . Apart from enzymatic reactions such as sialylation, removal of C‐terminal lysine, C‐terminal amidation etc., the majority of the charge variants are likely formed due to non‐enzymatic reactions varying with the environmental conditions such as pH, temperature, duration, etc.…”
Section: Charge Variantsmentioning
confidence: 74%
“…One such common reaction is asparagine deamidation. Non‐enzymatic deamidation of asparagine is one of the most common protein degradation pathways contributing to protein charge variants . There are cases where well‐separated peaks in the acidic region are formed completely due to deamidation .…”
Section: Charge Variantsmentioning
confidence: 99%